Differentiated approach to training loads planning in athletes based on the clinical form of mitral valve prolapse - O. B. Nekhanevych (Zaporožskij Medicinskij Žurnal)
Mitral valve prolapse is one of the most important small abnormalities of the heart, causing specialists’ interest in matters of admission to sports.